Biostability Assessment of Flexible Parylene C-based Implantable Sensor in Wireless Chronic Neural Recording. (2016) - Lecomte, A.; Degache, A.; Descamps, E.; Dahan, L.; Bergaud, C.
Abstract: The stability of polymer-based sensors in a biological environment remains a challenge, as delamination and swelling often compromise mechanical and electrical capability. We have developed a neural implant based on Parylene C, a biocompatible flexible polymer, with PEDOT-nanostructured gold patterns to record the brain electrical activity. Here, we show first evidence of device biostability through in vitro soaking tests in artificial brain environment and in vivo recording in mice. Our results indicate that after over the six months trial, more than 75% of the in vitro electrodes have stable impedance, and the implanted sensors in mice were able to accurately record signals from mice hippocampi. None of the implants presented with signs of Parylene degradation or metal corrosion. Overall, the devices are promising candidates for reliable, chronically implanted sensors in the biomedical field.